HLA-B and HLA-C Differ in Their Nanoscale Organization at Cell Surfaces - Kennedy, Philippa R.; Barthen, Charlotte; Williamson, David J.; Davis, Daniel M. (Frontiers in Immunology, 2019)
The particular HLA class I variants an individual carries influences their resistance and susceptibility to a multitude of diseases. Expression level and variation in the peptide binding region correlates with, for example, a person’s progression to AIDS after HIV infection. One factor which has not yet been addressed is whether or not different HLA class I proteins organize differently in the cell membrane on a nanoscale. Here, we examined the organization of three HLA-B allotypes (B*2705, B*5301 and B*5701) and two HLA-C allotypes (C*0602 and C*0702) in the membrane of 721.221 cells which otherwise lack expression of HLA-B or HLA-C. All these allotypes are ligands for the T cell receptor and leukocyte immunoglobulin-like receptors, but additionally, the HLA-B allotypes are ligands for the killer-cell immunoglobulin-like receptor family member KIR3DL1, HLA-C*0602 is a ligand for KIR2DL1, and HLA-C*0702 is a ligand for KIR2DL2/3. Using super-resolution microscopy, we found that both HLA-B and HLA-C formed more clusters and a greater proportion of HLA contributed to clusters, when expressed at lower levels. Thus, HLA class I organization is a covariate in genetic association studies of HLA class I expression level with disease progression. Surprisingly, we also found that HLA-C was more clustered than HLA-B when expression level was controlled. HLA-C consistently formed larger and more numerous clusters than HLA-B and a greater proportion of HLA-C contributed to clusters than for HLA-B. Thus, HLA class I variants are organized differently in the cell surface membrane which may impact their functions.